2021
DOI: 10.1111/jace.18036
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering for reduced large AC signal dielectric loss of PZT‐based hard piezoelectric ceramics

Abstract: A low dielectric loss value under large AC electric fields is highly desired for piezoelectric ceramics in high‐power applications. However, only a few reports have focused on studying or revealing the dielectric loss behavior and mechanism of piezoelectric ceramics under an AC electric field. In this work, x (Ca, Fe) co‐doped Pb0.96Sr0.04Zr0.53Ti0.47O3 (x = 0.0, 0.25, 0.5, 1.0, 1.5 mol.%) hard piezoelectric ceramics (PSZT‐xCF) were selected for investigation. The lowest dielectric loss (@ E = 500 V mm−1) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, because Ar atoms are used for etching and cleaning the sample surface before XPS testing, surface-OH and surface-absorbed H 2 O were excluded. 58 Therefore, the single peak OV can be attributed to oxygen vacancies. Therefore, the peak area ratio of OV to OL is used to calibrate the oxygen vacancy content.…”
Section: Resultsmentioning
confidence: 99%
“…However, because Ar atoms are used for etching and cleaning the sample surface before XPS testing, surface-OH and surface-absorbed H 2 O were excluded. 58 Therefore, the single peak OV can be attributed to oxygen vacancies. Therefore, the peak area ratio of OV to OL is used to calibrate the oxygen vacancy content.…”
Section: Resultsmentioning
confidence: 99%
“…6 The above results also indicated that under 50−500 V/mm AC electric fields, the high-field ε r and tan δ of PZMNZT-xFe ceramics were significantly larger than those under small-signal conditions (Figure 3A), considering the domain wall motion as the most important factor in the case of a high AC electric field. 23 Meanwhile, the defect mechanism of the PZMNZT-xFe ceramics was analyzed using the XPS spectra of the O1s valance state, as shown in Figure 5A-D. Asymmetric peaks were observed in all components, which could be fitted into three peaks using Gaussian-Lorentz function.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 15 studied the electrical properties of the Cu/Bi co-doped Pb(Mn 1/3 Sb 2/3 )O 3 -Pb(Zr,Ti)O 3 -based piezoelectric ceramics and achieved good performance with d 33 = 410 pC/N, Q m = 1478, k p = 0.62, ε r = 1550, and T c = 330 • C. In addition, many similar works have successfully obtained the good electrical parameters in PZT-based ceramics [16][17][18] and lead-free piezoelectric ceramics, [19][20][21] and provided a method for improving their electrical parameters. However, the quasi-static electrical parameters only partially reflect their high-power performance in practical applications, which is affected by many factors, such as temperature, 22 high field, 23 mechanical stress, 24 etc., so that the high-power performance of piezoelectric ceramics should still be necessarily explored. Yu et al 25 investigated the high-power performance of Bi(Ni 1/2 Ti 1/2 )O 3 -Pb(Mn 1/3 Nb 2/3 )O 3 -Pb(Zr,Ti)O 3 ceramics, which successfully obtained a high v 0 of 0.92 m/s, twice as high as that of commercial PZT4 ceramics (∼0.4 m/s).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of low-valence ions into perovskite lead zirconate titanate (PZT) piezoelectric ceramics, referred to as acceptor doping or hard doping, is an efficient way to raise the mechanical quality factor Q m of piezoelectric materials. , The prevailing consensus is that the introduced acceptor ions recombine with the oxygen vacancies created for the price balance to form defect dipoles, which can impede the movement of the domain wall and increase Q m . Unfortunately, acceptor doping increases Q m while d 33 drops …”
Section: Introductionmentioning
confidence: 99%
“…14 Unfortunately, acceptor doping increases Q m while d 33 drops. 15 Poling treatment is the last step in the preparation of piezoelectric ceramics. Before being polarized, piezoelectric ceramics do not exhibit piezoelectricity due to disorder in the ferroelectric domains.…”
Section: Introductionmentioning
confidence: 99%